Control of grid-connected inverter output current: a practical review - Avila, Victor Habermann (2022)
The number of grid-connected inverters is growing due to the expansion of the use of renewable energies (RE) systems and this may affect grid power quality and stability. Some control algorithms reduce injected current harmonics and add new possibilities to the converter. This paper implements and analyses the proportional integral (PI) controller in the synchronous frame and the proportional resonant (PR) controller with and without the harmonics compensators (HC). All these control strategies have proven to be effective and robust. However, the PR+HC controller presents better output current quality. The PI and PR controllers have similar performances. This work also compares the harmonic content of the current with the IEEE 1547 reference and with three commercial inverters from different manufacturers.